2018
DOI: 10.1002/anie.201808919
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Lewis Acid Catalyzed ortho Photocycloaddition of Olefins to Phenanthrene‐9‐carboxaldehydes

Abstract: Visible‐light irradiation (λ=457 nm) enabled the enantioselective ortho photocycloaddition of olefins to phenanthrene‐9‐carboxaldehydes (15 examples, 46–93 % yield, 82–98 % ee). A chiral oxazaborolidine Lewis acid (20 mol %) was employed as the catalyst. It operates by coordination to the aldehyde inducing a bathochromic absorption shift beyond the nπ* absorption of the uncomplexed aldehyde. At long wavelengths the Lewis acid complex is exclusively excited; within the complex, one enantiotopic face of the arom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(48 citation statements)
references
References 47 publications
0
48
0
Order By: Relevance
“…2018 , 57, 14593–14596 . 3 The study revealed that catalyst loadings in Lewis acid-mediated photocycloaddition reactions can be significantly lowered when securing that Lewis acid coordination leads to an extensive bathochromic shift. Aldehydes were for the first time employed in a photochemical reaction catalyzed by a chiral 1,3,2-oxazaborolidine Lewis acid.…”
Section: Key Referencesmentioning
confidence: 99%
See 2 more Smart Citations
“…2018 , 57, 14593–14596 . 3 The study revealed that catalyst loadings in Lewis acid-mediated photocycloaddition reactions can be significantly lowered when securing that Lewis acid coordination leads to an extensive bathochromic shift. Aldehydes were for the first time employed in a photochemical reaction catalyzed by a chiral 1,3,2-oxazaborolidine Lewis acid.…”
Section: Key Referencesmentioning
confidence: 99%
“…Along these lines, Stegbauer et al found that the bathochromic shift Δλ of phenanthrene-9-carboxaldehydes in the presence of EtAlCl 2 was larger than 70 nm, reaching beyond the nπ*-absorption of the uncomplexed substrate ( Figure 6 ). 3 …”
Section: Beyond Conventional Oxazaborolidines: New Catalysts and Reacmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] However,i ts applications in asymmetric dearomatization reactions are rare. [10] At the beginning, we noticed that highly reactive nitrosocarbonyl intermediates could be generated catalytically from bench-stable N-hydroxycarbamates in the presence of ap hotocatalyst under air. [11,12] Based on these results,o ur original design was to explore the natural nucleophilicity of indoles for chiral phosphoric acid catalyzed [13] asymmetric dearomatization with transient electrophilic nitrosocarbonyl species using visible-light as am ild driving energy force.…”
Section: Resultsmentioning
confidence: 99%
“…The first intermolecular example using this catalyst system used cyclic ketones 346 with alkenes 347 to synthesise bicyclic compounds 348 ( Scheme 58 ) [ 135 ]. A similar reaction was also later developed for the cycloaddition of phenanthrene-derived aldehydes 349 with alkenes 350 , using 457 nm excitation, which was possible due to the increased conjugation of the substrate, and a lower catalyst loading ( Scheme 58 ) [ 136 ].…”
Section: Reviewmentioning
confidence: 99%